1976
DOI: 10.3147/jsfp.10.243
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Intestinal Microflora of Salmonids

Abstract: Abstract:A study on the actual condition and changes of normal bacterial flora in the intestines of salmonids was carried out to determine the actual status of bacterial flora in the digestive tract, particularly in the intestines, in the course of their life cycle, i. e. migration from fresh water to the sea and back to the original river.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
2
5

Year Published

1978
1978
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(61 citation statements)
references
References 20 publications
(27 reference statements)
4
50
2
5
Order By: Relevance
“…However, this trend of relation ship was hardly achieved in this study as in the results obtained by Yoshimizu and Kimura (1976) when genus Vibrio formed as the dominant species in the intestines of salmonids cultured in seawater. The present result suggests the selective propagation of Vibrio species in the intestines of milkfish larvae.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…However, this trend of relation ship was hardly achieved in this study as in the results obtained by Yoshimizu and Kimura (1976) when genus Vibrio formed as the dominant species in the intestines of salmonids cultured in seawater. The present result suggests the selective propagation of Vibrio species in the intestines of milkfish larvae.…”
Section: Discussioncontrasting
confidence: 38%
“…To elucidate pathogenesis of these bacterial pathogens and assess the role of gastro intestinal microflora in several marine finfishes, intestinal microflora of larval and juvenile stages were investigated (Yoshimizu and Kimura, 1976;Muroga et al, 1987;Tanasomwang and Muroga, 1988). Results obtained varied each other showing that intestinal flora were influenced mainly by flora of food ingested and/or flora of the environment.…”
mentioning
confidence: 99%
“…Indeed, the dominance of vibrios was not recorded until the end of the larval stage [64]. The comparative lack of diversity in larvae continues into older fish, and it has been suggested that the flora may be subjected to as-yetundescribed selective effects leading to a restricted number of taxa being present [48,65,66,67,68].…”
Section: Microflora In the Digestive Tractmentioning
confidence: 99%
“…A comparatively wide range of taxa have been associated with the digestive tract of adult freshwater fish, and include Acinetobacter, Enterobacter, Escherichia, Klebsiella, Proteus, Serratia [32], Aeromonas [32,33,37,57,69,70 [4], Bacteroides [3,71,72], Citrobacter freundii [29], Hafnia alvei [69], Cytophaga/Flexibacter [57], Bacillus, Listeria, Propionibacterium, Staphylococcus [29], Moraxella [38], and Pseudomonas [4,29,57,68]. In one study involving pike perch, it was concluded that Moraxella and Staphylococcus were unique to the habitat when compared with the digestive tract of other fish species [38].…”
Section: Microflora In the Digestive Tractmentioning
confidence: 99%
“…Of the 126 bacterial strains isolated previously (Kamei et al, 1987c(Kamei et al, , 1988b (Yoshimizu and Kimura, 1976) or SA (Yamamoto et al, 1982) medium, then inoculated into CYG (Kamei et al, 1988b) or MCYG was removed and each well was inoculated with 100 PFU/0.2 ml of IHNV and allowed the virus to adsorb to the cells for 1 h and washed three times with 1 ml of Hanks' BSS. A mixture of 9 : 1 of overlay medium and each bacterial culture filtrate was prepared and 1 ml of this mixture was overlayed into each well.…”
Section: Bacterial Strainsmentioning
confidence: 99%